Employee Performance Assessment of PT.Satria Manunggal Petrolindo Using 360-Degree Feedback Method - Hartati, Tri; Hikmah, Noer (Politeknik Ganesha Medan, 2022)
PT Satria Manunggal Petrolindo is one of the partners in PT. Pertamina is engaged in the business of trading fuel oil. In running its business, PT Satria Manunggal Petrolindo has employees who are dedicated to their work. Employee performance at this company is one of the important aspects that need to be assessed related to efforts to improve performance and quality in achieving the company's business goals and objectives, where so far the assessment of employees is still using traditional appraisal methods. This assessment method causes some employees to feel uncomfortable and unmotivated at work so that employee productivity can decrease. With these problems, the authors conducted research on the performance of employees at PT Satria Manunggal Petrolindo. The method that will be used in measuring employee performance appraisal in the company is the 360-degree feedback method. This method uses comprehensive feedback from all levels around employees to assess performance according to work behavior which consists of five assessment components, namely: Self Appraisal, Manager Review, Peer Review, Subordinates Appraising Manager (SAM) and Customer/Client Review. The results of the research and evaluation of the problem in this study were the use of the 360-degree feedback method in evaluating employee performance. It is expected to be able to overcome the problems of employee performance appraisal so as to increase the comfort and work motivation of PT.Satria Manunggal Petrolindo which will have an impact on increasing the achievement of the company's business goals.